IMPLEMENTATION OF COOPERATIVE LEARNING METHOD IN IMPROVING LEARNING MOTIVATION IN MUTHOLAAH SUBJECTS CLASS VIIIB MTs UMMUL QURO AL-ISLAMI BOGOR - Nabila, Gina; Asriani, Asriani; Fahmi, Nurul (SHAWTUL ARAB, 2024)
This study examines the implementation of the Cooperative Learning Method to improve students' learning motivation in the Mutholaah subject. The background is the low learning motivation and students' dependence on memorizing textbook texts. The aim is to evaluate the effectiveness of the Cooperative Learning Method in improving the learning motivation of class VIII B Putri students at MTs Ummul Quro Al-Islami Bogor. The methodology used is Classroom Action Research (CAR) with four stages: planning, implementation, observation, and reflection. The subjects of the study involved 37 class VIII B Putri students. Data were collected through questionnaires and analyzed using percentage calculations. The results showed an increase in students' learning motivation. In the first cycle, 30 students (81%) achieved very good criteria, 6 students (16%) good criteria, and 1 student (3%) poor criteria. The second cycle showed a significant increase with all 37 students (100%) achieving very good criteria. The conclusion is that the implementation of the Cooperative Learning Method has proven effective in improving students' learning motivation in the Mutholaah subject, with an increase in performance from the first cycle to the second cycle